Bridging the data divide: Integrating social assistance systems in Jakarta during Covid-19 (BIS Humanities and Social Science, 2025)
This study examines the challenges and strategies of social welfare data integration in Indonesia, particularly in DKI Jakarta. It highlights the importance of reliable data for effective policy-making and service delivery in the public sector, emphasizing the role of master data management (MDM) in ensuring data quality and coherence. The research identifies significant obstacles such as data fragmentation, lack of standardization, inadequate technological infrastructure, and poor inter-agency coordination, which hinder efficient poverty alleviation efforts. The Jakarta Smart City initiative and applications like Jaki and CRM are explored as innovative approaches to improve data integration and community engagement. The study advocates for a comprehensive strategy that incorporates grassroots data collection, collaboration among stakeholders, and the adoption of best practices from other regions to enhance the effectiveness and equity of social welfare programs in alignment with the Sustainable Development Goals.